A Brief Review on the Opto-Electronic Properties of Delafossite Materials for Solar Cell Applications - Laltlanmawii, H.; Celestine, L.; Zosiamliana, R.; Bhattarai, S.; Tursunov, Mukhriddin E.; Dekhkonov, Avazbek T.; Pachuau, Z.; Rai, D. P. (Current Indian Science, 2025)
Delafossite materials have excellent properties, making them highly sought after for next-generation solar cells. They are based on abundant and non-toxic elements. Since environmental and economic factors are crucial in the pursuit of discovering a new solar energy harvester, extensive research has been conducted. This paper reviews various synthesis methods, crystal structure, and opto-electronic properties of delafossite materials. The calculated solar cell parameters, such as short-circuit current (Jsc), open-circuit voltage (Voc), and efficiency (η) of solar cells fabricated under diverse conditions, are reported. The findings indicate that these materials are ideal for use in solar cells, as they can function as photocathodes or photoanodes in p-type Dye-Sensitized Solar Cells (DSSCs) and also serve effectively in absorber layers and hole-transport layers. Their unique crystal structure, with a tunable band gap, allows for maximizing power conversion efficiency. However, there are still limitations in synthesizing nanoparticle structures to achieve desired properties, and improvements in various aspects and higher efficiency are still required.
Keywords: Renewable resource